Sn – Zn – Ga alloys for leadfree soldering obtained by rapid quenching - Shepelevich, Vasiliy G.; Gusakova, Olga V. (Journal of the Belarusian State University. Physics, 2020)
The paper presents the results of a study of the structural-phase state of the foil of eutectic near eutectic Sn – Zn alloys doped by Ga obtained by rapid melt quenching at a melt cooling rate of 105 K/s. Using the methods of X-ray diffraction analysis, scanning electron microscopy, and X-ray spectrometry, it was established that the foil solidifies with the formation of tin-based supersaturated solid solution and its microstructure is formed as a result of the decomposition of the solid solution by discontinuous mechanism at room temperature. The homogeneity of the composition and distribution of gallium and zinc inclusions over the volume of the foil was established. Using the electron backscatter diffraction technique, it was shown that the foils have a microcrystalline structure due to the deep supercooling of the melt, which leads to a high crystal nucleation rate. The grain size decreases depending on the distance to the mold. The increase in grain size is associated with a change in the solidification conditions over the thickness of the foil: deterioration of heat removal and a decrease in supercooling. There is no pronounced grain texture in the foils.